PENGARUH MOTIVASI TERHADAP PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN DI KANTOR KOPERASI SIMPAN PINJAM SEJAHTERA KECAMATAN TIKALA KOTA MANADO - Umaternate, Arfia; Rompas, Sonny; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
This research aims to to know how to influence the motivation of work (external and Internal) in theOffice of Cooperative Peace Subdistrict Tikala then to know the motivations which are the most influential inthe labor productivity of the employees at the Office of Cooperative Peace Tikala Subdistrict. Given theimportance of motivation, then a form of management's attention on the issue of employee motivation inworking is to do business with the way giving motivation in employees in certain business through a series ofcooperative in accordance with the policy of the cooperative, so the motivation of employees in work will bemaintained. To motivate employees, cooperative leader should know the motives and motivations that aredesired by those employees increased productivity is essentially a process terminating an alloy of variousinterests.The methods used in this research is quantitative methods. With the technique of gathering researchlibrary and field research. In the study which became population is thriving, Cooperative Office employee atSub Tikala totalling 54 people. That becomes the variable X (Motivation) and becomes the variable Y(Motivational performance).From the results of the analysis, the results obtained that external motivation (working conditions, agood Boss, Financial and social Assurance) gives influence in the improved productivity performance of thecooperative. While the analysis obtained from internal motivation (a job that is fun, challenging Work, andinteresting work) exert influence in increasing productivity. External and internal motivation effectsimultaneously on performance of employees. This is proven by the regression coefficient of externalmotivation is greater than internal motivation. The influence of motivation in organization of higher employeeto productivity, so as to enhance cooperative targets set. Then recommend to the company in order tomaximize internal motivation. Because when the external and internal motivation is given with a balancedemployee then it is definitely on the rise. The company should pay more attention to external motivation oncommunication between the employee and the employer, when an employee feels comfortable with theautomatic communication of their work productivity increased. A leader should pay attention to the rights ofemployees who perform by giving rewards to motivate employees, satisfying the needs of individuals in theorganization. Employee motivation should be heeded by the leadership, so that the specified targets or in theexpected by the company can be accomplished according to demands of the company.Keys words: Motivation, increased work productivity